Painful scar endometriosis after caesarean section - Gaur, Indu; Kumar, Kanishka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Scar endometriosis is an extremely rare phenomenon. We presented a case of scar endometriosis in a thirty one year old patient (P2L2) who developed swelling and cyclical pain in the previous suprapubic caesarean scar (of previous two caesarean sections) area lasting for 10 days every month for last 2 years. On abdominal examination she had a small swelling at right margin of the wound which was firm and tender on examination with dull aching constant pain at the site of examination. This pain used to aggravate with menses. Investigations suggested scar endometriosis and she was treated medically with oral contraceptives and GnRH but symptoms recurred on stopping the treatment. Patient underwent surgery. A dense fibrotic tissue of 5×4×5 cm size including the rectus sheath, part of rectus muscles and subcutaneous tissue was found on the right side of the old previous scar beneath the skin which was excised and sent for histopathological examination which reconfirmed the diagnosis of scar endometriosis with presence of glands and stroma in the excised tissue. Post-operative period was uneventful.